Mental health in times of challenges and setbacks: a review - Tomaz, Marcilea; Rodrigues Caputo, Lara; Bernardes Bedim, Vanisse; José de Oliveira Duarte, Marco (Argumentum, 2020)
This article is an interrogative review of articles in Brazilian magazines on the area of Social Work around the theme of mental health in times of challenges and setbacks. It sets out the historical context of the Brazilian Psychiatric Reform to date. Then, for the interrogative review, it starts with data obtained from a selection of magazines in the area, focusing on six of them: Serviço Social & Sociedade, Katálysis, Revista de Políticas Públicas, Argumentum, Textos & Contextos and O Social em Questão. Using the following descriptors: mental health, public policies, trends, and setbacks, it analyses sixteen articles. The analysis focuses on the dismantling of public policies on mental health, alcohol, and other drugs, in the context of the worsening crisis of the neoliberal state and the emergence of neoconservatism and questions the challenges of the resistance to confronting it.